A Consolidated Tree Structure Combining Multiple Regression Trees With Varying Depths, Resulting in an Efficient Ensemble Model - Ashoor Mahani, Elmira; Ziarati, Koorush (Informatica, 2023)
Regression is a commonly used technique to predict a continuous target value based on a set of input features. Decision trees are hierarchical models that offer high interpretability, fast and precise reasoning, and are also used for regression tasks. However, determining the optimal stopping conditions for decision trees is a complex problem that has attracted significant research interest. Ensemble based modeling is an effective approach for adjusting hyper-parameters, where base models with varying parameter values are combined instead of searching for the best value. Random forests are a classic example of an ensemble model that combines decision trees generated from different perspectives. This paper proposes a novel approach that generates base trees using the same tree-generation procedure, but with different stopping conditions. Unlike random forests, this model can be efficiently integrated into a single tree structure. Additionally, the paper proposes some aggregation methods based on weighting the base models. Experimental results on standard datasets demonstrate that the proposed method outperforms well-known stopping conditions.